Albumin metabolism following partial hepatectomy in the rat - Lloyd, Elwyn Allden (UCT/MRC Liver Research Centre, 2018)
In the work reported here the author set out to investigate five aspects of albumin metabolism following partial hepatectomy in the rat. 1. The plasma albumin levels following partial hepatectomy. 2. The effect of partial hepatectomy on the albumin synthesis rate. 3. The effect of supplementary amino acids on the albumin synthesis rate following partial hepatectomy. 4. The effect of hydrocortisone on the albumin synthesis rate following partial hepatectomy. 5. The effect of partial hepatectomy on the albumin catabolic rate.